Legal Responsibility of Obstetric and Gynecological Doctor for Abortion with Indication of Fetal Deffects - Widyasih Pritasari; Sri Mugirahayu; Askan; Mohammad Zamroni; MokhamadKhoirul Huda (Institute of Medico-legal Publications Pvt Ltd, 2021)
An undeveloped fetus in the mother’s womb leads to congenital disabilities where the baby can be fully dependent on his mother. Fetal defects in the Health Law are included in medical emergencies to be treated with full requirements and provisions regulated by law. Article 32 paragraph (1) points (a) and (b) of the Government Regulation on Reproductive Health explains the scope of indications of medical emergencies include a condition where it threatens the lives of mothers and babies and babies with disabilities where it resulted in a difficult for the baby to live outside the womb or the condition where the baby has some defects and cannot be cured. Article 75 paragraph (2) of the Health Law states if doctors do an abortion with indications of a medical emergency such as the fetus suffering from a severe genetic disease or congenital defects, the doctors cannot be convicted. So the principle of prudence is needed in determining the diagnosis to bring off an abortion because abortion is closely related to crime if it is not appropriately treated.